Impact of Quality of Life, Social Awareness and Political Willingness on Prevention from HIV/AIDS in Pakistan: A Mediation and Moderation Model - Khan, Saima Sardar; Azhar, Tehseen; Ali, Rashid; Shahid, Muhammad Naeem (Pakistan Journal of Humanities and Social Sciences, 2023)
Currently, modern world is focusing on the control of fatal diseases including HIV/AIDS. However, in developing countries these diseases are spreading rapidly. There are various factors, which encourage HIV/AIDS. One of the major reasons is lack of awareness among public. In Pakistan, scholars did not discuss the role of awareness about HIV/AIDS as a prevention tool. This study is one of the efforts to observe the impact of quality of life, social awareness and political will on the prevention of HIV/AIDS in Pakistan. Majority of the past literature concentrated on the issue of HIV/AIDS; however, there is paucity of literature on highlighting the major factors of HIV/AIDS prevention. Therefore, this is one of the few studies, which formally investigated the major factors contributing towards the prevention of HIV/AIDS, particularly in the Sind province of Pakistan. A questionnaire was utilized to collect the data. Partial Least Square (PLS 3)-Structural Equation Modeling (SEM) was used to analyze the data. It is found that political willingness, social awareness and quality of life has a significant relation with HIV/AIDS prevention. In order to formulate the strategy, this study is important for governments and NGOs to consider social awareness, government willingness and quality of life as a tool to prevent HIV/AIDS in Pakistan.